Pengaruh penggunaan pankreas kambing awetan terhadap kekuatan tarik dan kemuluran kulit kras kambing - Lutfi, Muchtar (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1991)
Took 10 pieces salted goat skins which same quality, cut in 20 sides follow the back bone line devided into 5 groups, each group consist 4 sides. All this sample be processed to crust leather accorfing to IRDLAI procedure. In tbating processing the substitute for oropon was cured of goat pancreas.For 5 groups sample each used 0; 0,75 ;1,5 ; 2,25 and 3 procentage of cured pancreas. For tensile strength and stretch testing used the part of croupon, shoulder and belly. Analisis static using CRD nested sample and factorial 3 Ã 5 and subsequently be done Tukey test. There was a real differences (P<0,01) betweem temsile strength by effects of concentration of pancreas also with itâs stretch.The best consentration can be suggested were 0,75 ; 1,5 ; 2,25 procentage. Average tensile strength for each of them were 183,2 Kg/cm2 ; 177,3 Kg/cm2 and 207,1 Kg/cm2, and the stretch wich close with the standart only on the concentration 2,25% that was 66,6%.